Morphological and Physiological Characterization of Listeria monocytogenes Subjected to High Hydrostatic Pressure - Ritz, M. (American Society for Microbiology, 2001)
High hydrostatic pressure is a new food preservation technology known for its capacity to inactivate spoilage and pathogenic microorganisms. That inactivation is usually assessed by the number of colonies growing on solid media after treatment. Under normal conditions the method does not permit recovery of damaged cells and may underestimate the number of cells that will remain viable and grow after a few days in high-pressure-processed foodstuffs. This study investigated the damage inflicted on Listeria monocytogenes cells treated by high pressure for 10 min at 400 MPa in pH 5.6 citrate buffer. Under these conditions, no cell growth occurred after 48 h on plate count agar. Scanning electron microscopy, light scattering by flow cytometry, and cell volume measurements were compared to evaluate the morphological changes in cells after pressurization. All these methods revealed that cellular morphology was not really affected. Esterase activity, as assessed either by enzymatic activity assays or by carboxy fluorescein diacetate fluorescence monitored by flow cytometry, was dramatically lowered, but not totally obliterated, under the effects of treatment. The measurement of propidium iodide uptake followed by flow cytometry demonstrated that membrane integrity was preserved in a small part of the population, although the membrane potential measured by analytical methods or evaluated by oxonol uptake was reduced from −86 to −5 mV. These results showed that such combined methods as fluorescent dyes monitored by flow cytometry and physiological activity measurements provide valuable indications of cellular viability.